Viabilidade bioeconômica do sistema semi-intensivo de produção de pacu em tanque escavado - Rabaioli, Adelita (2020)
Aquaculture is the fastest growing food production sector in the world. In Brazilian fish farming, native species have been standing out. Pacu (Piaractus mesopotamicus) has fast growth, tasty meat, excellent fillet yield, ease of handling and acceptability of the feed. The objective of this study was to evaluate the bioeconomic viability of monoculture of pacu in a semi-intensive system in an excavated tank. Cultivation was carried out for 15 months in an excavated tank, where 783 juvenile pacu were stored, with an average weight of 52 ± 16g (0.32 fish / m2); fish were fed twice a day (morning / afternoon) until apparent satiety using extruded commercial feed. During cultivation, data collections and biological samples were performed. Subsequently, bromatological, biochemical and water quality analyzes were performed. Monitoring of variable costs and crop revenues was also carried out to analyze economic viability. Indicators such as Internal Rate of Return (IRR), Net Present Value (NPV), Profitability Index (IL) were analyzed. At the end of cultivation, the average individual weight gain was 1.350 kg, equivalent to a biomass of 4.093 kg / ha. The yield of fillet with skin of fish was 55.24%, and of carcass, 85.01% and feed conversion of 2: 1. The project proved to be economically viable, with NPV of R $ 10,904.36, IRR of 18% and IL of R $ 2.77. The results of the study indicate that the semi-intensive system of breeding pacu in monoculture can be an important alternative as a complementary income in fish farming, especially for small producers.